Reduction of Transmission Losses based on Optimal Power Flow using Genetic Algorithm - Rahul, Jinendra; Sharma, Yagvalkya; Birla, Dinesh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
This paper presents the application of GeneticAlgorithm (GA) for solving optimal power flow problems. It is animportant tool for performance analysis of many power systemsproblems. Optimal power flow (OPF) is of very muchsignificance in power system operation analysis underderegulated environment of electricity industry. The OPFoptimizes a power system operating objective function, whilesatisfying a set of system operating constraints. The basic OPFsolution is obtained with production cost minimization as theobjective function and the optimal settings of the power systemare determined. OPF can also be formulated for reactive poweroptimization, as minimization of system active power losses andimproving the voltage stability in the system. In the presentpaper objective function is to reduce transmission losses usingGA, a IEEE 30-bus test power system is studied for optimalpower flow. It is described in the paper that GA based optimalpower flow can provide optimal solution